Hubungan Efikasi Diri dengan Kecemasan Akademik Pada Siswa Kelas 12 SMAIT X - Zaidan Lukmanul Hakim; Sarita Candra Merida; Tugimin Supriyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to examine the relationship between self-efficacy and academic anxiety among twelfth-grade students at SMAIT X. This study employed a quantitative approach with a correlational research design. The sample consisted of 82 students selected using a saturated sampling technique. Data were collected using a self-efficacy scale based on Bandura's (1997) theory and an academic anxiety scale based on the dimensions proposed by Cassady and Johnson (2002). Data were analyzed using the Pearson Product Moment correlation test with IBM SPSS Statistics version 29. The results showed a significant negative relationship between self-efficacy and academic anxiety (r = -0.361, p < 0.001). These findings indicate that the higher the students' self-efficacy in dealing with academic demands, the lower their academic anxiety, and vice versa. Therefore, self-efficacy is significantly associated with academic anxiety among twelfth-grade students at SMAIT X..